Pengaruh Pendidikan dan Penggangguran Terhadap Kemiskinan di Jakarta Timur - Ramadhan, Dhia; Ginting, Andi Lopa (Economie: Jurnal Ilmu Ekonomi, 2025)
Countries around the world, especially in developing countries, are struggling with poverty. The definition of poverty is a complex problem that is influenced by several interrelated elements, such as unemployment rates and education levels, and whether or not these issues have an impact on poverty, especially in East Jakarta. This study aims to determine the relationship between unemployment and education with poverty in East Jakarta from 2018 to 2022. Secondary data used in this study comes from time series data, namely information from the East Jakarta Central Statistics Agency regarding community unemployment, the number of poor people, and the gross participation rate at the high school level in East Jakarta. Using the Eviews12 application, multiple linear regression analysis was used to process the data. The findings of this study indicate that, at the same time, the level of education significantly reduces poverty in East Jakarta.